A CONTENT ANALYSIS OF ENGLISH LEARNING MODULE BY CUNNINGSWORTH’S THEORY - Viera Safira; Yanti Wirza; Lenny Kristanti; Hana Shadrina; Surya Aulia Sukarman (Universitas PGRI Palembang, 2024)
The control over the materials used in the classroom rests with the schools. Because of this, some educational establishments decide to develop their own curricula. When developing the module, schools must follow educational guidelines in addition to ensuring that the learning resources align with the curriculum. This study aims to evaluate and investigate the English curriculum used in one of the middle schools. This study will use a qualitative descriptive research method in conjunction with a qualitative research design. When evaluating an English module for third-grade junior high school students, the Cunningsworth evaluation checklist will offer a comprehensive framework for a general examination and analysis of the module. The research yielded several findings. The linguistic substance of the language style is appropriate for the pupils' grade level. This skill set does not include any writing or listening tasks. The topic analysis indicates that the programme is engaging and exciting, and that there is a significant overlap between the subject matter and the students' daily life. In theory as well as in practice, this research would be helpful. In theory, this study should enhance education, especially in the field of assessing instructional materials for the English language. Additionally, it might support or add to previous findings. It is hoped that this research's practical application will help educators evaluate instructional resources, and English language instructors will find value in the findings. This study examines and assesses English content produced by the school, filling the evaluation gap left by earlier studies that evaluated widely used or education government textbooks. It is expected to assist schools in evaluating their land as a source of instructional materials to facilitate effective instruction.